Respuesta :
Solve for [tex]|2x-1|[/tex]:
[tex]2|2x-1|-8=18\implies2|2x-1|=26\implies|2x-1|=13[/tex]
Now if [tex]2x-1\ge0[/tex], we have [tex]|2x-1|=2x-1[/tex] and
[tex]2x-1=13\implies2x=14\implies x=7[/tex]
On the other hand, if [tex]2x-1<0[/tex], then [tex]|2x-1|=-(2x-1)=1-2x[/tex] and
[tex]1-2x=13\implies-2x=12\implies x=-6[/tex]
➣ Assignment: [tex]\bold{Solve \ Equation: \ 2\left|2x-1\right|-8=18}[/tex]
↔↔↔↔↔↔↔↔
➣ Answer: [tex]\boxed{\bold{x=-6, \ x=7}}[/tex]
↔↔↔↔↔↔↔↔
Explanation: ↓↓↓↓↓
↔↔↔↔↔↔↔↔
➤ [ Step One ] Add 8 To Both Sides
[tex]\bold{2\left|2x-1\right|-8+8=18+8}[/tex]
➤ [ Step Two ] Simplify
[tex]\bold{2\left|2x-1\right|=26}[/tex]
➤ [ Step Three ] Divide Both Sides By 2
[tex]\bold{\frac{2\left|2x-1\right|}{2}=\frac{26}{2}}[/tex]
➤ [ Step Four ] Simplify
[tex]\bold{\left|2x-1\right|=13}[/tex]
➤ [ Step Five ] Apply Absolute Rule
Note: [tex]\bold{Absolute \ Rule: \ \mathrm{If}\:|u|\:=\:a,\:a>0\:\mathrm{then}\:u\:=\:a\:\quad \mathrm{or}\quad \:u\:=\:-a}[/tex]
[tex]\bold{2x-1=-13\quad \mathrm{or}\quad \:2x-1=13}[/tex]
➤ [ Step Six ] Simplify Equations
[tex]\bold{2x-1=-13: \ x=-6}[/tex]
[tex]\bold{2x-1=13: \ x \ = \ 7}[/tex]
➤ [ Step Seven ] Combine Solutions
[tex]\bold{x=-6, \ x=7}[/tex]
↔↔↔↔↔↔↔↔
[tex]\bold{\rightarrow Mordancy \leftarrow}[/tex]